Analisis Kemampuan Literasi Numerasi Siswa Kelas XII dalam Menyelesaikan Soal Seleksi Nasional Berdasarkan Tes (SNBT) di SMA Swasta Cerdas Murni - Rahmah, Atika; Asrul, Asrul (Jurnal Pendidikan Matematika : Judika Education, 2025)
ABSTRACT. This study aims to reveal deeper students’ numeracy literacy skills in solving the National Selection Based on Tests (SNBT) questions. This research was conducted at SMAS Cerdas Murni in the even semester of the 2024/2025 academic year. The research subjects consisted of 25 students of class XII MIPA-3. The research uses qualitative-methods with a descriptive approach. The research instruments used were SNBT test questions and interviews. The results showed that the numeracy literacy skills of class XII MIPA-3 students varied across each question. In question number 1, students' skills were classified as very low, as they still struggled to simplify complex problems despite understanding basic mathematical concepts. For question number 2, students demonstrated good skills, especially in applying formulas related to sequences and series and in drawing conclusions from implicit information. Question number 3 was rated as excellent, as students were able to process data from tables accurately and correctly apply probability concepts. Question number 4 fell into the fair category, as students could read graphs and perform calculations, but their ability to identify patterns or anomalies was still limited. Lastly, in question number 5, students showed good results with adequate skills in interpreting visual data and drawing conclusions from graphs. Overall, students' numeracy literacy skills were categorized as fair in solving SNBT (National Selection Based on Test) questions.   Keywords: Numeracy Literacy, Ability, SNBT Questions.